Linkage Between Preceding August Asian–Pacific Oscillation and September Precipitation Over Southeast China - Xia, Changji; Hua, Wei; Hu, Qin; Yang, Kaiqing; Ming, Jing; Wu, Xiaofei; Fan, Guangzhou (Frontiers in Earth Science, 2022)
Understanding the spatiotemporal variation of autumn precipitation and its relationship with the large-scale circulation is important for planning industrial and agricultural production, economic development, and ecological protection. This study investigated the relationship between the August Asian–Pacific Oscillation (APO) and September precipitation over Southeast China (SC) during the period 1961–2020. Results showed that the August APO can exert considerable control on September precipitation over SC and that a significant positive correlation exists between them. With a strong (weak) August APO, the anomalous southerly (northerly) winds are observed in the north (south) of SC at the upper level, and the deep trough over East Asia and ridge over North Pacific at 500hPa are both reinforced (weakened). This leads to anomalous northward (southward) lower-tropospheric winds over the East Asian coast, accompanied by enhanced convergence (divergence) of warm and cold air masses and anomalous ascent (descent) motion which results in more (less) precipitation over SC. The underlying mechanism can be explained as thermal anomalies induced by the APO that can persist from August to September, which modulates the atmospheric circulation anomalies in September and eventually causes more (less) precipitation over SC. Therefore, in addition to the role of sea surface temperature forcing on precipitation variations, our analyses suggest that the preceding temperature anomalies at the middle and upper troposphere also should be considered as an important precursory factor for the following precipitation over SC.